Head and Neck Free Flap Reconstruction in an Academic versus a Community Setting - Lewcun, Joseph; Massand, Sameer; Trangucci, John; Shen, Chan; Johnson, Timothy S. (Journal of Reconstructive Microsurgery, 2021)
Background Head and neck free flap reconstructions are complex procedures requiring extensive resources, and have the potential to be highly morbid. As such, it is imperative that they should be performed in an appropriate setting, optimizing outcomes while limiting morbidity. The aim of this study is to identify any disparities in the treatment outcomes of patients undergoing head and neck free flap reconstruction by a single surgeon in an academic versus a community hospital setting.Methods A retrospective review of all patients who underwent head and neck free flap reconstruction for any indication by a single surgeon from 2009 to 2019 was conducted. All surgeries were performed at one of two hospitals: one academic medical center and one community hospital. Demographics and rates of partial or complete flap failure, medical complications, surgical complications, mortality, and other secondary outcomes were compared between the two settings.Results Ninety-two patients who underwent head and neck free flap reconstruction were included. Fifty-seven (62%) of free flap reconstructions were performed in the academic medical center, while 35 (38%) were performed in the community hospital. There were no significant differences in complete flap loss, either intraoperative or postoperative (p = 0.5060), partial flap loss (p = 0.5827), postoperative surgical complications (p = 0.2930), or medical complications (p = 0.7960) between groups. The in-hospital mortality rate was 0% (n = 0) at the university hospital as compared with 5.7% at the community hospital (p = 0.0681). The mean operative time was 702.3 minutes at the university hospital and 606.3 minutes at the community hospital (p = 0.0080).Conclusion Head and neck free flap surgery can be performed safely in either an academic or a community setting, with no difference in primary outcomes of surgery. Preferential selection of either treatment setting should be based on consideration of patient needs and availability of auxiliary specialty services.
Keywords: free flap reconstruction; head and neck; community hospital; surgical outcomes